An exploration of decision aid effectiveness: the impact of promoting affective vs. deliberative processing on a health‐related decision - Davis, Esther L. (Health Expect, 2014)
BACKGROUND: Decision aids (DAs) are non‐directive communication tools that help patients make value‐consistent health‐care decisions. However, most DAs have been developed without an explicit theoretical framework, resulting in a lack of understanding of how DAs achieve outcomes. OBJECTIVE: To investigate the effect of promoting affective vs. deliberative processing on DA effectiveness based on dual‐process theory. DESIGN, SETTING AND PARTICIPANTS: One hundred and forty‐eight female university students participated in a randomized controlled experiment with three conditions: emotion‐focused, information‐focused and control. Preference‐value consistency, knowledge, decisional conflict and satisfaction were compared across the conditions using planned contrast analyses. INTERVENTION: The intervention comprised two different DAs and instructional manipulations. The emotion‐focused condition received a modified DA with affective content and instructions to induce an affective reaction. The information‐focused and control conditions received the same DA without the affective content. The information‐focused condition received additional instructions to induce deliberative processing. RESULTS: Controlling for the experiment‐wise error rate at P < 0.017, the emotion‐focused and information‐focused conditions had significantly higher decisional satisfaction than the control condition (P < 0.001). The emotion‐focused condition did not demonstrate preference‐value consistency. There were no significant differences for decisional conflict and knowledge. DISCUSSION: Results suggest that the promotion of affective processing may hinder value‐consistent decision making, while deliberative processing may enhance decisional satisfaction. CONCLUSIONS: This investigation of the effect of affective and deliberative processes in DA‐supported decision making has implications for the design and use of DAs. DA effectiveness may be enhanced by incorporating a simple instruction to focus on the details of the information.